Lifestyle attributes and academic performance in physical education - Cruz, Tom Bangtong (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This study evaluated the lifestyle attributes of the second year Bachelor of Physical education students in terms of rest and recreation, eating habits, stress management, and physical activity. This study answered the following questions: What is the lifestyle attributes of the second year Bachelor of Physical Education students in terms of Rest and Recreation, Eating Habits, Stress Management, and Physical Activity? What is the Academic Performance of college students in Physical Education subjects? Is there a significant relationship between the Lifestyle attributes and the Academic Performance in Physical education subjects? The study was conducted in one of the universities in Bukidnon province. There were 108 participants in the study. The researcher used descriptive statistics analysis such as mean and SD, frequency and percentage, and Pearson- Product Correlation for the third problem. Stress management obtained the highest total mean, while eating habits obtained the lowest total mean. The dominant number of respondents obtained a “very high satisfactory” level. Also, only one respondent got the highest level “excellent” and also one got the lowest level “moderately satisfactory.” The result shows that there is a significant relationship between physical activity and academic performance in the physical education subject. Physical activity and academic performance have a positive correlation.